A CURRENT APPLICATION OF THE METHODS OF SECULAR AND STATISTICAL PARALLAX - Turner, D. G. (Одеські астрономічні публікації, 2012)
The methods of secular and statistical parallax for homogeneous groups of Galactic stars are applied in a practical (classroom) exercise to establish the luminosity of bright B3 V stars. The solar motion of 20 km s-1 relative to group stars exceeds their random velocities of ±10 km s-1, a condition adopted for preference of secular parallax to statistical parallax. The group parallax of πups = 5.81 ± 0.83 mas and derived luminosity MV = -0.98 ± 0.33 for B3 V stars from upsilon components of proper motion should be close to the true value. The weighted mean Hipparcos parallax of < π Hip> = 5.75±0.27 mas for the same sample, and implied luminosity of MV = -1.00 ± 0.15, confirm the secular parallax solution. Both solutions are close to MV = -0.83 for ZAMS stars of the same type, implying that Malmquist bias in the selection of stars mainly accounts for the presence of unresolved binaries, slightly evolved objects, and rapidly rotating stars in the sample.